Caregiver contribution to self‐care and its associated variables among caregivers of ostomy patients: Results of a cross‐sectional study. Issue 1 (13th June 2021) - Giordano, Vittoria; Iovino, Paolo; Corvese, Francesco; Vellone, Ercole; Alvaro, Rosaria; Villa, Giulia
Abstract: Aims and objectives: To describe caregiver contribution (CC) to ostomy self‐care and identify its associated variables among caregivers of ostomy patients. Background: Self‐care is essential for ostomy patients, but it can be difficult to perform. In these cases, caregivers play a key role in promoting self‐care behaviours. So far, the CC to ostomy self‐care has not been investigated thoroughly. Design: This is a cross‐sectional and multicentre study conducted at seven outpatient clinics of two Italian regions. Methods: We recruited 252 caregivers between February 2017–May 2018. The Caregiver Contribution to Ostomy Self‐Care Index (CC‐OSCI) was used to measure CC to ostomy self‐care. Three multivariable linear regression models were fitted to identify variables associated with CC dimensions (maintenance, monitoring and management). The STROBE checklist was used to report the present study. Results: The sample (mean age = 58.73, SD = 13.98) was mostly female (80.60%), unemployed (58.70%) and resided with the patient (81.00%). Caregivers being employed and those declaring more hours of contribution per week were associated with a significantly lower contribution to self‐care maintenance. Caregivers with lower levels of education and those residing with the patient were less likely to contribute to CC to self‐care monitoring. Spousal caregivers and those with higher preparedness contributed significantly lower to CC to self‐care management. Conclusions: We found a variety of sociodemographic factors associated with CC to ostomy self‐care. Relevance to clinical practice: Sociodemographic variables associated with CC to ostomy self‐care can help clinicians develop more tailored educational interventions for caregivers who find their contribution challenging.